Fibroblast growth factor 21: a novel metabolic regulator with potential therapeutic properties in obesity/type 2 diabetes mellitus - Dostálová, Ivana; Haluzíková, Denisa; Haluzík, Martin (Physiological research, 2009)
Fibroblast growth factor 21 (FGF21) is a novel metabolic regulator produced primarily by the liver that exerts potent antidiabetic and lipid-lowering effects in animal models of obesity and type 2 diabetes mellitus. This hormone contributes to body weight regulation and is strongly involved in the response to nutritional deprivation and ketogenic state in mice. The principal sites of metabolic actions of FGF21 are adipose tissue, liver and pancreas. Experimental studies have shown marked improvements in diabetes compensation and dyslipidemia after FGF21 administration in diabetic mice and primates. Positive metabolic actions of FGF21 without the presence of apparent side effects make this factor a hot candidate to treat type 2 diabetes and accompanying metabolic diseases. The aim of this review is to summarize the current knowledge about the metabolic effects of FGF21 including some preliminary data on changes of its levels in humans with a special emphasis on its therapeutic potential in type 2 diabetes mellitus.
Keywords: financování organizované; Animals; fibroblastové růstové faktory; Diabetes Mellitus, Type 2; Obesity; energetický metabolismus; Fibroblast Growth Factors; lidé; Hypoglycemic Agents; Energy Metabolism; signální transdukce; diabetes mellitus 2. typu; látky proti obezitě; Signal Transduction; Anti-Obesity Agents; Financing, Organized; hypoglykemika; obezita; modely nemocí na zvířatech; Disease Models, Animal; zvířata; Humans